Endogenous FGF21-signaling controls paradoxical obesity resistance of UCP1-deficient mice - Susanne Keipert (Nature Portfolio, 2020)
Brown adipose thermogenesis increases energy expenditure and relies on uncoupling protein 1 (UCP1), however, UCP1 knock-out mice show resistance to diet-induced obesity at room temperature. Here, the authors show that this resistance relies on FGF21-signaling, inducing the browning of white adipose tissue.